OP0025 Autologous Hematopoietic Stem Cell Transplantation in Systemic Sclerosis is Effective in Inducing Prolonged Remission of Disease Activity: Results from Long-Term Follow-Up. (10th June 2014) - Zaccara, E.; Maglione, W.; Onida, F.; Annaloro, C.; Saporiti, G.; Giordano, R.; Sambataro, D.; Cavalieri, S.; Cortelezzi, A.; Del Papa, N.
Abstract : Background: A therapy really successful in modifying the natural history of Systemic Sclerosis (SSc) has not so far been described. Conversely, autologous haematopoietic stem cell transplantation (AHSCT) has demonstrated to be sometimes an effective treatment in patients (pts) with severe (s) diffuse cutaneous (dc) SSc. Objectives: We report a retrospective analysis of our experience with AHSCT in severe cutaneous SSc evaluating the efficacy on skin and major organ involvement. In addition, we focused on the results of AHSCT on SSc clinical activity by using a validated activity score. Methods: Rodnan skin score (mRSS), assessment of heart and lung organ involvement (OI) by echocardiography, respiratory functional parameters (VC, DLCO), and disease activity level, by the European Scleroderma Study Group (ESSG) scoring system, represented the tools used for selecting and monitoring the pts. Pts were eligible if they had a rapidly progressive disease, a mRSS>14, and ESSG score>3, in the absence of severe advanced OI. AHSCT was performed using positively selected CD34+ cells. Mobilisation was performed with CTX 4000 mg/m 2 and G-CSF 10 μg/m 2 /day. Conditioning regimen included CTX 50 mg/kg/day and rabbit ATG 2.5 mg/kg/day. Results: Since 2003, 17 pts s-dcSSC were enrolled (4 M, 13 F; median age 40 yrs., ranging 20–62 yrs.), The median follow-up was of 41 months (range 6–136). A beneficial effect was observed in 16/17 pts (94%).The mean mRSS was 20.9 (SD ± 4.0) at baseline (T0), 9.8 (± 4.6) at month 6 (T6), 6.8 (± 2) at month 12 (T12), and 3.0 (± 1.6) at month 60 (T60), (all p<0.001 with respect to T0). The mean ESSG score was 5.2±0.7 at T0, 2.1±0.8 at T6, 2.1±1.8 at T12, and 1.8±0.74 at T60 (all p<0.0001 with respect to T0). OI was nearly unchanged during follow-up. Mean DLCO predicted value was 65.7%±16.8% at T0, 63.2%±12.5% at T12, and 59.8%±16.3% at T60. Mean VC predicted value was 78.7%±22.0% at T0, 83.4%±17.0% at T12, 90.3% ± 26.0% at T60. No echocardiographic changes were identified during follow-up. Two patients died from SSc-related lung and cardiac disease progression, and one patient because of interstitial pneumonia within 100 days after AHSCT, this leading to a TRM of 5.8%. Conclusions: This study confirms that AHSCT in selected patients with severe dcSSc results in sustained improvement of skin thickening and stabilizations of organ function up to 10 years after transplantation, so leading to a global clinical improvement, as showed by the persistent reduction in the ESSG clinical activity score. According to other experiences, TRM resulted reasonable, as a possible result of patients selection. These findings are in keeping with the view that AHSCT is effective in improving the inflammatory and active phase of SSc, while letting unchanged and stable the fibrosclerotic one. Further studies are needed to evaluate the importance of CD34 selection, the need of immunosuppressive therapy post-AHSCT and the best timing of HSCT in the treatment of SSc patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4375